Shocks, groups, and networks in Bukidnon, Philippines - Quisumbing, Agnes R.; McNiven, Scott; Godquin, Marie (International Food Policy Research Institute, 2008)
This study examines the role of groups and networks in helping poor Filipinos manage their exposure to risks and cope with shocks. It brings together two strands of literature that examine how social capital affects economic variables and investigate the processes by which social capital formation, participation in networks and groups, and trusting behavior comes about. Using a longitudinal study from a province in Northern Mindanao, Philippines, the authors find that households belong to a number of formal and informal groups and networks, but participation differs according to household characteristics. Households belonging to the lower asset quartiles belong to fewer groups, and households with more human and physical capital have larger social networks. Furthermore, wealthier households are more likely to take part in productive groups while membership in civic and religious groups is not limited by economic status. Migrant networks play an important risk-smoothing role via remittances sent by migrant daughters.